2019
DOI: 10.35826/ijoess.2484
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on the Relationship Between Primary School Teachers' Self-Efficacy B

Abstract: The purpose of this research is to investigate whether there is a significant relationship between attitudes and self-efficacy beliefs of primary school teachers towards gifted education; the level of Self-Efficacy Belief and Attitude and whether they differ according to various variables. In the study, correlational survey model was employed in order to determine a relationship between attitudes and self-efficacy beliefs of primary school teachers towards gifted education. Two scales were used in the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In this study, when the self-efficacy of classroom teachers regarding the education of gifted students was examined in terms of gender, it was concluded that there was a differentiation in favour of men in the personality trait subdimension. When the literature was examined, it was found that different results were reached and that there was no significant difference between the attitudes and self-efficacy of classroom teachers towards gifted students and the gender variable (Güneş, 2015;Dinçer, 2019), as well as research findings (Girgin & Şahin, 2019;Vatansever Bayraktar, Kadıoğlu Ateş & Afat 2019;Yıldız, 2020) showing that male teachers' self-efficacy for the education of gifted students is higher than female teachers. In another study, it was concluded that women's self-efficacy levels in Mentoring and Responsibility dimensions were statistically significantly higher than men (Abanoz, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this study, when the self-efficacy of classroom teachers regarding the education of gifted students was examined in terms of gender, it was concluded that there was a differentiation in favour of men in the personality trait subdimension. When the literature was examined, it was found that different results were reached and that there was no significant difference between the attitudes and self-efficacy of classroom teachers towards gifted students and the gender variable (Güneş, 2015;Dinçer, 2019), as well as research findings (Girgin & Şahin, 2019;Vatansever Bayraktar, Kadıoğlu Ateş & Afat 2019;Yıldız, 2020) showing that male teachers' self-efficacy for the education of gifted students is higher than female teachers. In another study, it was concluded that women's self-efficacy levels in Mentoring and Responsibility dimensions were statistically significantly higher than men (Abanoz, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%